Auctions: Theory and Practice. - Klemperer, P (Nuffield College (University of Oxford), 2004)
This book is a non-technical introduction to auction theory; its practical application in auction design (including many examples); and its uses in other parts of economics. It can be used for a graduate course on auction theory, or - by picking selectively - an advanced undergraduate or MBA course on auctions and auction design. Part A introduces the basic theory. Part B shows how modern auction-theoretic tools illuminate a range of mainstream economic questions that are superficially unconnected with auctions. Part C discusses practical auction design. Part D describes the one-hundred-billion dollar 3G mobile-phone license auctions. None of the writing is technical, except in the Appendices. The material was presented as the inaugural (2003) Toulouse Lectures in Economics and is forthcoming at Princeton University Press. This document contains the Contents, Preface and Introduction to the book. A draft of the FULL BOOK is available at http://www.paulKlemperer.org.